PENGETAHUAN IBU BALITA TERHADAP PEMBERIAN IMUNISASI DIFTERI LENGKAP DI DESA GILI KETAPANG PROBOLINGGO: Case Study: Knowledge Of Women Of Under-Children On Giving Complete Diphtheria Immunization In Gili Ketapang Village, Probolinggo - Rumaisih, Rumaisih; Rohmatin, Homsiatur; Widayati, Agustina (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
The knowledge or cognitive of mothers under five about Diphtheria is the dominant which is very important for the formation of a person's behavior (Over Behaviour) so as to produce a decision to carry out a complete diphtheria immunization.This research is a correlational analytical research, as for the research design using cross sectional, where it is carried out to measure the relationship of a number of populations through samples. So that it contains information about the relationship between the knowledge of mothers of toddlers aged 24-59 months and the completeness of providing Diphtheria immunization in Gili Ketapang Village, Sumberasih District, Probolinggo Regency which will be held from June to August 2022 with a total population of 363 mothers of toddlers aged 24-59 months, and a sample of 54 respondents taken by means of Cluster Random Sampling. Data collection using questionnaire sheets and MCH books, which include coding, editing, and tabulating, then the data is analyzed manually and computer with a chi-square test. The results of this study found that the average knowledge of mothers of toddlers aged 24-59 months in Gili Ketapang Village was mostly sufficient with a percentage of 61.36%. Meanwhile, the provision of DPT immunization to toddlers aged 24-59 months is mostly incomplete with a percentage of 51.85%. Based on the results of the Bivariate analysis with the Chi Test, P-Value values were obtained: 0.00 and a= 0.05 meaning r < a, thus showing that there is a Relationship Between the Knowledge of Mothers of Toddlers Aged 24-59 Months About Diphtheria Immunization with the Completeness of Diphtheria Immunization. The conclusion of this study is that there is a significant relationship between the Knowledge of Toddler Mothers Aged 24-59 Months About Diphtheria Immunization and the Completeness of Diphtheria Immunization In Gili Ketapang Village, Sumberasih District, Probolinggo